Acute interstitial pneumonia (hamman-rich syndrome) - a life threatening respiratory disease - Siddiqui, Md Mahmudur Rahman; Rahman, Md Mostafizur; Siddiqui, Md Abdul Moyeed; Masum, Hasan Ali; Giasuddin, Rubayat Shekh (Bangladesh Journal of Medicine, 2018)
Acute interstitial pneumonia (AIP) is an idiopathic lung disease characterized by rapidly progressive dyspnoea, respiratory failure developing over days to weeks in patients without pre-existing lung disease. AIP show a very poor prognosis, with high mortality and remains unfamiliar to physicians. In this report, we present a case of a mid-age male with AIP who, was treated with intensive medical facilities, still showed a rapid progressive clinical deterioration, and eventually died of respiratory failure. Bangladesh J Medicine Jul 2017; 28(2) : 91-94